GESTATIONAL WEIGHT GAIN DEPENDS ON THE INITIAL ANTHROPOMETRIC VALUES - N. B. Chabanova; T. N. Vasilkova; T. P. Shevlyukova (Акушерство, гинекология и репродукция, 2017)
The aim was to study whether the increase in body weight during pregnancy depends on the initial anthropometric values. Materials and methods. This prospective study included 100 pregnant women; the measurements of their height, body weight, and BMI were made at the start and then on the 1st, 2nd and 3rd trimesters of pregnancy. Results. In the overweight/ obese women, an excessive weight gain during pregnancy is more common than that in the women with initial weight deficiency or those with normal weight. The least gestational weight gain was found in pregnant women with obesity. At the same time, the obese women showed more deviations from the WHO-recommended gestational body weight gain as compared with the women with normal or low initial weights. Conclusion. The magnitude of gestational weight gain depends on the initial BMI. With the increase in BMI the incidence of excessive gestational weight gain increases.